Service experience using DNA analysis for genetic prediction in Duchenne muscular dystrophy. Issue 1 (January 1988) - Goodship, J; Malcolm, S; Robertson, M E; Pembrey, M E
Abstract : In August 1985 we instituted a carrier and prenatal testing service for Duchenne muscular dystrophy (DMD) using direct DNA analysis. The experience over the first nine months is described. We have analysed samples for RFLPs from 154 people including 53 women at risk of being DMD carriers from 37 families. We used the probes pERT87.8 (BstXI and TaqI polymorphisms), 87-15 (TaqI polymorphism), and pXJ1.1 (TaqI polymorphism). Forty-one of the women have had their risks altered. We found one deletion (pERT87-8) out of 23 DNA samples analysed from affected boys. We used a recombination fraction of 0.05 in risk calculations but did not detect any known crossovers. In nine of the families there is only an isolated case of DMD. In families where we have not been able to alter the risk of the women being a carrier (for example, because all brothers are dead), we have offered prenatal exclusion and have carried out one first trimester prenatal diagnosis on this basis. Lowering the risk of an affected fetus to less than 2.5% appears to be a satisfactory situation for many (most) of the women involved and seems to justify the introduction of genetic prediction based on single intragenic probes despite the 5% recombination frequency.